Les métamorphoses du monstre. Le satyre dans l’Aminta et ses traductions françaises jusqu’au milieu du XVIIe siècle - Françoise Lavocat (Etudes Epistémè)
The originality of Aminta’s Satyr in relation to his predecessors on the Italian stage goes without question. The genealogy of its speech (in the monologue of act II, scene 1) and the farcical scene of the nymph being attacked (told by Tirsi in act III, scene 1) reveals Theocritus’ influence, which is ambivalent: the imitation of the fourth eclogue of Theocritus’ Idylles has the Satyr speaking the lines of a monster figure, the Cyclops. But the discourse on love and bees which constitutes the opening lines of the Satyr’s monologue, also situate its amorous wail as universal (which also confirms the use of this motif in the illustrations of the play’s Aldina editions).The Satyr’s role is then examined in several French translations and imitations of the Aminta towards the end of the sixteenth and seventeenth centuries. It appears that satyr-like speech can be entirely relegated to the shepherd (as is the case in Trage-Comédie pastorale by Bassencourt, 1594), or to another monster (such as the centaur in Du Mas’ Lidie, 1609).These transformations are interpreted as indicating an intense questioning of the hybrid status. Moreover, the article examines the stakes of the choice made by Aminta’s translators, Rayssiguier (1631) and Toussaint Quinet (1638), in depicting the near rape of Silvia. A study of engravings by Daniel Rabel confirms the main hypothesis, which is that the role of the satyr makes a dramatic turn toward the unequivocal farce (which dispels the pastoral’s troubling game of mirrors between satyrs and shepherds). Similarly, the spectacular mode tones down the scene’s eroticism and considerably simplifies ambiguities.